Effect of social learning on smoking - Herken, Hasan; Özkan, İshak; Çilli, Ali S.; Telcioğlu, Metin; Kucur, Rahim (Journal of Dependence, 2000)
Object: Cigarette, is the most common substance making dependency. While its diffusion is decreasing in developed countries, it is increasing in developing count ries.Th is study was done to establish possible things that make reduction in cigarette using diffusion by searching the effect of social learning on cigarette using behavior of young people.Method: The study was done among 1559 students between 12-21 ages in secondary, high schools, apprentice education centers in Konya center containing all social groups by Selçuk University Psychiatry clinic. A questionnaire is applied asking whether people being close or taken as examples by young people consume cigarette or not. Results are evaluated by chi-square test in the program of SPSS for windows 5.0.Results: It is found that boys consume more cigarette than girls, ones whose elder brothers consuming cigarette consume more than others whose elder brothers not consuming cigarette; ones whose teachers or masters they like consuming cigarette consume it more than the others whose teachers or masters they like not consuming it, young’s whose ideal artists and football players consuming cigarette consume more than the others whose ideal artists and football players not consuming it.Conclusion: It is found that social learning in cigarette using behavior has very important place. In prevention of starting cigarette using and in giving it up, if people who are taken example by yoth (mother, father, brother, teacher, master, artist, sportsman, film star)don’t use cigarette, it may be effective.
Keywords: Youngs; smoking; social learning